Source Geometry and Rupture Characteristics of the 20 February 2023 Mw 6.4 Hatay (Türkiye) Earthquake at Southwest Edge of the East Anatolian Fault - Yolsal-Cevikbilen, Seda; Taymaz, Tuncay; Irmak, Tahir Serkan; Erman, Ceyhun; Kahraman, Metin; Ozkan, Berkan; Eken, Tuna; Ocalan, Taylan; Dogan, Ali Hasan; Altuntas, Cemali (AMER GEOPHYSICAL UNION, 2024)
Following the catastrophic 6 February 2023 Mw 7.8 and Mw 7.6 Kahramanmara & scedil; earthquakes in the East Anatolian Fault Zone (EAFZ; southeast T & uuml;rkiye), numerous aftershocks occurred along the major branches of this left-lateral shear zone. The spatio-temporal distribution of the earthquakes implied the stress-triggering effects of co-seismic ruptures on closely connected fault segments over large distances. On the 20 February 2023 two earthquakes with Mw 6.4 and Mw 5.2 struck Hatay (T & uuml;rkiye) located near the Samanda & gbreve;-Antakya segment of the EAFZ. To understand the rupture evolution of these earthquakes, we first re-located the aftershock sequence that occurred over a 3-month period in the Hatay-Syria region. A normal faulting mechanism with a significant amount of left-lateral strike-slip component at a shallow focal depth of 12 km was estimated for the 2023 Mw 6.4 earthquake from the inversion of seismological data. Our slip models describe a relatively simple and unilateral rupture propagation along about 36 km-long active segments of the EAFZ. The co-seismic horizontal displacements inferred from the Global Navigation Satellite System data are compatible with the oblique slip kinematics. Furthermore, we suggest that this earthquake did not produce notable tsunami waves on the adjacent coasts since the rupture plane did not extend to the seafloor of the Eastern Mediterranean with substantial amount of vertical displacement. We reckon that a future large earthquake (Mw >= 7.0) in the Hatay-Syria region where increased stress was transferred to the fault segments of the EAFZ and the Dead Sea Fault Zone (DSFZ) after the 2023 earthquakes will be a probable source of tsunami at the coastal plains of the Eastern Mediterranean Sea region. The destructive 6 February 2023 Mw 7.8 and Mw 7.6 SE T & uuml;rkiye earthquakes triggered an intense seismic activity along the major segments of the East Anatolian Fault Zone (EAFZ) in SE T & uuml;rkiye. On 20 February 2023, distinct earthquake clusters occurred along the Amanos and Samanda & gbreve;-Antakya segments in the southwest edge of the EAFZ. In this manuscript, source characteristics and rupture kinematics of the 20 February 2023 Mw 6.4 Hatay (T & uuml;rkiye) earthquake were estimated by analyzing seismological and geodetic data. Our results mainly indicate a normal faulting mechanism with a significant amount of left-lateral strike-slip component for this earthquake. The slip models show a simple slip distribution pattern along the strike of the fault plane that lasted about 10-12 s. The analyzed time series of the available Global Navigation Satellite System stations present horizontal co-seismic displacements consistent with oblique slip kinematics of the rupture. We finally suggest that this earthquake serves as a reminder of the seismic and tsunami hazard potential in the Hatay-Syria area. The 20 February 2023 Mw 6.4 Hatay (T & uuml;rkiye) earthquake indicates a normal fault mechanism with a significant left-lateral strike-slip component Transtensional deformation is evident in the Hatay-Syria (SE T & uuml;rkiye) region Most of the 2023 Hatay-Syria aftershocks appear to concentrate on the depth range of 10-20 km of the crust
Keywords: East Anatolian Fault Zone; earthquake source parameters; active tectonics; kinematic slip inversion; space geodesy; WAVE-FORM INVERSION; DEAD-SEA FAULT; SOURCE PARAMETERS; JOINT INVERSION; HISTORICAL EARTHQUAKES; MODERATE EARTHQUAKES; FOCAL MECHANISMS; CYPRUS ARCS; GPS DATA; TURKEY; Geochemistry & Geophysics